Teachers as workers and the creative work ethic in education research. Issue 2 (28th January 2023) - Hadar, David
Abstract: This article aims to raise education researchers' self-reflection about their treatment of teachers as workers through introducing the term "creative work ethic." At its core, the creative work ethic is the belief that good work entails innovation. Additional features of this ethic are the prizing self-motivation, work done individually, and a flexible schedule that mixes labor with leisure activities. The danger of the creative work ethic is a tendency for self-exploitation and devaluing workers who do not fit into the ethic. After defining the features of the creative work ethic and describing its drawback, the paper reads closely three education papers in order to show how this ethic colors their analysis of teachers' work or their prescription for better teaching.